Formation of the Plural of Names to â€œMissalâ€ of Gjon Buzuku, Compared with Todayâ€™s Albanian - Ã‡aushi, Elvira (Richtmann Publishing, 2012)
This study has as a purpose to show the ways for the formation of the plural of names in albanian language, tools used andhow they have changed, from Buzuku 1555 until nowadays. To show this thing, it is used the scientific research method and use of tabs,issued by the first albanian book â€œMissalâ€. It is seen that, the names in albanian, have a particular theme for the plural. There are manynames who form the plural as in todayâ€™s Albanian, but there are some names to Buzuku that donâ€™t have the same changes in todayâ€™sAlbanian.